Working Around the Problem: The Impact of Being Overweight and Obese on the Treatment of Clinical Illness - Sarel Brand; Linda Brand; De Wet Wolmarans (South African Family Practice)
Overweight and obesity are not only two highly prevalent conditions in the South African society, but they also contribute to 6 of the 10 most common causes of death. Further, being overweight not only results in significant metabolic and endocrine disturbances, it also changes how patients respond to most pharmacotherapeutic interventions for clinical illness. The present paper will attempt to elucidate some of the most common physio-pathological phenomena associated with being overweight and obese. We will briefly focus on the manner in which especially excessive visceral adipose tissue contributes to an altered physiological state and pharmacokinetic profile, while highlighting important clinical aspects of comorbid conditions that are frequently observed in this patient cohort.